Production of basil (Ocimum basilicum L.) seedlings under different substrates - Alves, Thatiane Nepomuceno (2021)
The aim of the study was to evaluate the effects of different substrates on the production of seedlings of basil (Ocimum basicilicum L.). The experimental design was completely randomized, with five types of substrates (Carolina®, Provaso®, Provaso® + Coconut fiber, Coconut fiber + Peat and Coconut fiber), being studied in two cultivars, Basilicão (BS) and Grecco a Palla (GP), with four replications. The evaluations were carried out from the fifth day after the emergency. The emergency speed index (IVE) and emergency percentage (E%) were calculated. The final evaluation was at 30 days after sowing (DAS), being analyzed the following variables: neck diameter (cm), plant height (cm), root length (cm), dry mass of the aerial part (g), dry root mass (g), number of leaves, leaf area (cm²) and quality index ofDickson (IQD). It was observed that, for the two BS and GP cultivars, the Carolina® substrate was the one that provided the highest percentage of emergence, as well as the lowest mean time of emergence. For height, stem diameter, number of leaves and leaf area, it was observed in both cultivars that the substrates, Coco fiber® and Coco fiber + Peat, were smaller. For root length, coconut fiber was superior for BS and coconut fiber + peat for GP. Taking into account all the morphological characteristics analyzed, in cv. BS Provaso® and Coconut fiber were the best for cv. GP was the coconut fiber + peat.